(untitled) (Palíndromo, 2026)
This article investigates the notion of material excess in Iberê Camargo’s painting based on the author’s experience of photographing details of the artist’s works at the Iberê Camargo Foundation in 2020. The analysis articulates the idea of “abundant matter”, traditionally associated with Camargo’s painterly facture, with Daniel Arasse’s theory of the detail, particularly the concept of the “cumulation of painting” (comble de peinture). The study proposes a connection between this notion and Louis Marin’s concept of the pictorial sublime, understood as the internal excess of representation over itself. From this theoretical framework, the article discusses how the detail, by disrupting the balance of the whole, produces an event of painting that displaces the viewer from the classical distance of vision. In Camargo’s work, this process manifests itself in the accumulation of paint, in the bodily struggle with the pictorial surface, and in the growing opacity of representation. The article also examines the artist’s relationship with European tradition, his rejection of formless, his tragic stance toward painting, and the link between sublimity, melancholy, and Romantic heritage. Thus, the material excess of Camargo’s painting is understood as a site of tension between form and matter, tradition and representational failure, where the sublime emerges as both fascination and limit.